Restorasi Direk Kelas IV Komposit dengan Palatal Putty Index pada Gigi Insisif Sentral Atas - Fajria Maulidina; Denny Nurdin (YARSI Dental Journal, 2026)
Introduction: More than 75% of tooth fracture cases occur in the maxillary area, and nearly half of these involve the incisors. Fractures in these teeth not only impair function but also significantly affect the patient’s aesthetics. In restoring the shape and function of the central incisors, there is a high demand for both precision and aesthetics. One approach that can be used is the palatal putty index technique. The aim of this case report is to discuss Class IV direct composite restoration treatment on teeth 11 and 21 using a putty index to achieve optimal anatomical form, which is often difficult to accomplish with a free-hand placement technique. Case Report: An 18-year-old male patient came to the conservative dentistry clinic at RSGM Unpad with a complaint of fractured upper front teeth due to physical trauma during a concert. Examination revealed fractures on teeth 11 and 21 extending to the dentin. Treatment was performed using Class IV direct composite restoration with the aid of a putty index. The procedure included tooth preparation, impression taking, wax-up fabrication on a working model, and the creation of a putty index to guide the restoration. Discussion: The putty index allows the operator to form restorations that are precise, aesthetic, minimally invasive, and cost-effective. This technique is especially beneficial in cases of significant anterior tooth structure loss, particularly when the palatal structure, contour, and tooth shape are compromised. Conclusion: The use of a putty index has proven effective in achieving precise and aesthetic tooth contours in a minimally invasive manner, especially in cases with considerable structural loss.